Nutrition Education “SAGARI” (Check Your Waist Circumference) as an Attempt to Prevent Adolescents’ Obesity - Megah Stefani; Athiya Fadlina (Universitas Padjadjaran, 2023)
The incidence of obesity at all ages in Indonesia, including adolescents, has increased. Obesity has a negative impact on physical and social health in adolescents. Excessive food consumption and lack of physical activity are risk factors for obesity in adolescents. Based on this urgency, it is necessary to prevent obesity in adolescents. The purpose of this Community Service activity was to increase adolescents’ understanding of the importance of the 4 pillars of balanced nutrition in efforts and to change attitudes by measuring waist circumference regularly to prevent obesity. Increasing knowledge and attitudes to prevent obesity was obtained by providing a Nutrition Education Program named